2019
DOI: 10.1016/j.bandc.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Young children in different linguistic environments: A multimodal neuroimaging study of the inferior frontal gyrus

Abstract: Magnetic resonance imaging (MRI) studies show that bilingual adults display structural and functional brain alterations, especially in the inferior frontal gyrus (IFG), dependent on when they learned their second language. However, it is unclear whether these differences are due to early exposure to another language, or to lifelong adaptation. We studied 22 children aged 3-5 years growing up in a multilingual environment and 22 age- and sex-matched controls exposed to an English-only environment. Resting-state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…Finally, Thieba, Long, Dewey and Lebel ( 2019 ) compared 3-to-5-year-old children raised in a multilingual environment to children raised in a monolingual environment. The two groups were matched on age, sex, and both maternal education and household income (measures of socioeconomic status).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Thieba, Long, Dewey and Lebel ( 2019 ) compared 3-to-5-year-old children raised in a multilingual environment to children raised in a monolingual environment. The two groups were matched on age, sex, and both maternal education and household income (measures of socioeconomic status).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous and early sequential multilinguals appear to demonstrate greater connectivity between the dACC and the fronto-parietal network (Becker et al, 2016) and reduced coupling between the dACC and right IFG (Thieba et al, 2019). These changes are accompanied by increased left IFG activity and decreased dACC activity in response to conflict (Garbin et al, 2010;Rodríguez-Pujadas et al, 2014).…”
Section: Linguistic Variabilitymentioning
confidence: 94%
“…Functional connection strengths from dACC to dlPFC and the striatum increased in early bilinguals and decreased in monolinguals when mentally applying new task rules (Becker et al, 2016). In contrast, resting-state connectivity between the right IFG and dACC was weaker in young multilingual compared to monolingual children (Thieba et al, 2019). This suggests that early multilingualism may alter the developmental trajectory of the dACC, such that the degree to which the dACC decouples from the fronto-parietal network and integrates with the cinguloopercular network is reduced in multilinguals.…”
Section: Multilingual Experience Affects the Cingulo-opercular Networkmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies have shown that atypical brain functions combined with information about alterations in brain structure explained better symptom severity in children with ADHD (Zhan et al, 2017; Wu et al, 2019). Another example concerns the evaluation of the brain correlates of math or language learning after instruction or intervention where a combination of anatomy and function information provided more accurate explanations than functional information alone (Supekar et al, 2013; Evans et al, 2015; Thieba et al, 2019), and proven to be useful in explaining the co-occurrence of reading and mathematical difficulties in children (Skeide et al, 2018).…”
Section: Introductionmentioning
confidence: 99%